Pelvic Incidence–Lumbar Lordosis Mismatch Is Predisposed to Adjacent Segment Degeneration After Single-Level Anterior Lumbar Interbody Fusion: A Retrospective Case-Control Study - Sun Geon Yoon; Hyung Chang Lee; Sang-Min Lee (Neurospine, 2023)
Objective Spinopelvic parameters play important roles in clinical outcomes and disability after short-segment fusion surgery for degenerative spine disease. This study aimed to investigate the relationship between preoperative or postoperative spinopelvic parameters and symptomatic adjacent segment degeneration (ASD) after single-level anterior lumbar interbody fusion (ALIF) surgery at the L4–5 segments. Methods All patients who underwent single-level ALIF at the L4–5 level from January 2010 to December 2013 and were followed up for 5 years were analyzed. We collected the degree of degeneration at adjacent segments and preoperative and postoperative spinopelvic parameters. We compared the preoperative and postoperative parameters between patients with and without symptomatic ASD. Results Sixty-one patients were included in our study, and 30 patients had symptomatic ASD. Degeneration at adjacent segments and preoperative spinopelvic parameters did not affect the occurrence of symptomatic ASD. Patients with symptomatic ASD had higher postoperative pelvic tilt (PT) and a mismatch between lumbar lordosis (LL) and pelvic incidence (PI) compared to those without. Postoperative PT > 15° and PI–LL mismatch > 10° were significant risk factors for symptomatic ASD. Conclusion High PT and PI–LL mismatch were significant risk factors for symptomatic ASD after single-level ALIF surgery. Spine surgeons should consider achieving proper LL to insert the cage at the appropriate angle and prevent a PI–LL mismatch value > 10° after single-level fusion surgery.